Case of stillbirth due to infection with Listeria monocytogenes - Beck, A. (1966)
A case of listeriosis in a stillborn baby is described. The causative organism was isolated from lung, placenta, and meconium. The only manifestation of infection of the baby's mother was a slight pyrexia three days before delivery which subsided quickly after treatment with ampicillin. Examination of the mother 11 days after delivery failed to produce evidence of listerial infection.